Uniqueness Solution of the Finite Elements Scheme for Symmetric Hyperbolic Systems with Variable Coefficients - Aloev, RD; Davlatov, SO; Eshkuvatov, ZK; Long, NMAN (Univ Putra Malaysia Press, 2024)
The present work is devoted to the proof of uniqueness of the solution of the finite elements scheme in the case of variable coefficients. Finite elements method is applied for the numerical solution of the mixed problem for symmetric hyperbolic systems with variable coefficients. Moreover, dissipative boundary conditions and its stability are proved. Finally, numerical example is provided for the two dimensional mixed problem in simply connected region on the regular lattice. Coding is done by DELPHI7.